2022
DOI: 10.3390/math10101702
|View full text |Cite
|
Sign up to set email alerts
|

Complex Dynamic Behaviour of Food Web Model with Generalized Fractional Operator

Abstract: We apply a new generalized Caputo operator to investigate the dynamical behaviour of the non-integer food web model (FWM). This dynamical model has three population species and is nonlinear. Three types of species are considered in this population: prey species, intermediate predators, and top predators, and the top predators are also divided into mature and immature predators. We calculated the uniqueness and existence of the solutions applying the fixed-point hypothesis. Our study examines the possibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In fact, the investigations of the mathematical properties of fractional derivatives give rise to the so-called fractional calculus (FC) which has received increasing interest by engineers, scientists and economists, who become able to make more realistic descriptions and precise analyses for their related real-world problems using the aid of FC [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. The high importance of the FC in mathematical modeling is due to its highest adequacy for measuring the natural phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the investigations of the mathematical properties of fractional derivatives give rise to the so-called fractional calculus (FC) which has received increasing interest by engineers, scientists and economists, who become able to make more realistic descriptions and precise analyses for their related real-world problems using the aid of FC [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. The high importance of the FC in mathematical modeling is due to its highest adequacy for measuring the natural phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…In the current century, many engineers, scientists, and economists have described and analyzed their related problems using the aid of fractional calculus (FC) [1][2][3][4][5][6][7][8][9]. The primary rationale is that using FC provides a greater level of accuracy when measuring natural phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most studies assumed that the number of individuals is a constant, i.e., birth and death are not considered. But the spread of some epidemics can influence population size, such as the birth of individuals leading to the growth of the network and the death leading to the reduction of the network [15][16][17][18][19][20][21][22]. Li et al [21] proposed a SIRS epidemic model with births and deaths and found that the basic reproduction number was an important factor influencing the dynamics of the network-based SIRS model.…”
Section: Introductionmentioning
confidence: 99%